Ecotoxicity of wastes in avoidance tests with Enchytraeus albidus, Enchytraeus crypticus and Eisenia fetida (Oligochaeta) - Kobetičová, Klára; Hofman, Jakub; Holoubek, Ivan (Waste management, 2010)
Contact bioassays are important for testing the ecotoxicity of solid materials. However, survival and reproduction tests are often not practical due to their duration which may last for several weeks. Avoidance tests with soil invertebrates may offer an alternative or extension to the classic test batteries due to their short duration (days rather than weeks) and due to a sensitive sub-acute endpoint (behavior). The aims of our study were: (a) to evaluate the effects of three solid industrial wastes (incineration ash, contaminated wood chips and contaminated soil) on three Oligochaeta species (enchytraeids Enchytraeusalbidus, Enchytraeus crypticus and earthworm Eisenia fetida) in avoidance tests; (b) to compare the sensitivity among the species and to compare results of avoidance test to reproduction tests; (c) to elucidate if measuring the weight in the earthworm avoidance test could be reasonable additional endpoint. Avoidance mostly increased with the increasing percent of waste in the mixture showing a dose-response curve. E. fetida was the most sensitive species and E. crypticus the least one. An additional endpoint, (changes in weight after two-day exposure) was not found to be more sensitive than avoidance reaction, but it confirmed that earthworms staying in the highest concentrations of the waste mixture were affected showing apparent weight reduction. Our results indicate that avoidance tests with earthworms and enchytraeids are feasible for waste testing.
Keywords: Oligochaeta; druhová specificita; Environmental Monitoring; monitorování životního prostředí; Reproduction; ekotoxikologie; látky znečišťující životní prostředí; učení vyhýbat se; vztah mezi dávkou a účinkem léčiva; Biological Assay; biotest; reprodukovatelnost výsledků; Species Specificity; průmyslový odpad; rozmnožování; Body Weight; Reproducibility of Results; Avoidance Learning; Animals; Toxicity Tests; zvířata; testy toxicity; Industrial Waste; Environmental Pollutants; Ecotoxicology; studie proveditelnosti; Dose-Response Relationship, Drug; tělesná hmotnost; Feasibility Studies